Study on the pathology and parasitic affection of liver in sheep and cattle at Mosul area - I. I. Al-Sultan (University of Baghdad, College of Veterinary Medicine, 1999)
A sample of (700) seven hundred out of (3000) three thousand randomly collected livers of sheep and cattle from Mosul abattoir during a biweekly visits of six months period , has been subjected to both grads and histopathological examinations.